2015
DOI: 10.1017/s1368980015003559
|View full text |Cite
|
Sign up to set email alerts
|

Water intake and beverage consumption of pre-schoolers from six European countries and associations with socio-economic status: the ToyBox-study

Abstract: Objective: To study the quantity and quality of water intake from beverages among pre-schoolers and investigate associations with gender and socio-economic status (SES). Design: Kindergarten-based cross-sectional survey within the large-scale European ToyBox-study. A standardized protocol was used and parents/ caregivers filled in sociodemographic data and a semi-quantitative FFQ. Setting: Kindergartens in six European countries (Belgium, Bulgaria, Germany, Greece, Poland and Spain). Subjects: European pre-sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 49 publications
0
23
0
1
Order By: Relevance
“…Since an unhealthy beverage intake was already found at preschool age and lower SES preschoolers were found to make unhealthier beverage choices than their high SES peers [1], it is important to investigate the underlying mechanisms of these SES-differences in intake to avoid the widening of health inequalities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since an unhealthy beverage intake was already found at preschool age and lower SES preschoolers were found to make unhealthier beverage choices than their high SES peers [1], it is important to investigate the underlying mechanisms of these SES-differences in intake to avoid the widening of health inequalities.…”
Section: Discussionmentioning
confidence: 99%
“…A recent European study in preschoolers showed that only about half of water intake from beverages was derived from plain water (both tap and bottled water without any additives) and nearly a quarter of total water intake from beverages from sweetened beverages (such as soft drinks and especially prepacked fruit juice) [1]. The excessive intake of added sugars through these sweetened beverages can lead to an energy imbalance (i.e., energy intake that exceeds energy expenditure) and thus to overweight [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note is that males reported, in all analyses, a significantly higher frequency of soft drink consumption compared with females (per school type, per age, and including all ages). This higher consumption of soft drinks in males has been reported several times [Kassem and Lee, 2004;Pinket et al, 2016;Scully et al, 2017] and suggests that genderspecific interventions should be applied for the prevention of this high consumption of soft drinks.…”
Section: Discussionmentioning
confidence: 59%
“…As shown in Table 1, once smoothie data is extracted and analysed separately intakes become lower-37 ml daily amongst 3½ to 5½ years olds [4]. Unfortunately, smoothie intake data amongst UK adults is not reported in Years 5 and 6 of the UK National Diet and Nutrition Survey (NDNS).…”
Section: Introductionmentioning
confidence: 99%